Analisis Variasi Tafsir Corak Nusantara Al-Iklil fi Ma’ani al-Tanzil: Variation Analysis of Archipelago Pattern in Tafsir Al-Iklil Fi Ma’ani Al-Tanzil - Subaidi,; Ahmad, Nehru Millat; Siti Marpuah,; Tantowi, Ahmad; Al-Mufti, Alex Yusron (Journal of Quranic Sciences and Research, 2023)
This study is discusses the interpretation of KH Misbah Musthofa works. entitled al-Iklil fi Ma'ani al-Tanzil. In this tafsir using the tahlili method and patterns from this tafsir if seen from several opinions have several patterns, but in this writing the writer incorporates Sufistic patterns and al-Ijtima'i manners. In interpreting a verse KH. Misbah Mustofa has a lot through ratio (bi al-Ray'i). The purpose of this study is for the community to always be guided by the Qur'an in life in the world. In addition, this interpretation also criticizes a lot about problems or events that occur in the community.. As the author exemplifies the prohibition of Family Planning or family planning. According to KH. Misbah Musthofa by relating the event to the story of Pharaoh. This study is qualitative with a literature analysis from the Qur'an. The results of the study show that the interpretation of al-Iklil fi Ma'ani al-Tanzil is one of the interpretations that have an archipelago pattern with its interpretation using Javanese pegon characters. In his interpretation, KH. Misbah Musthofa always explains the meaning of verses clearly and in detail, for example the relationship of a verse with verses and hadiths. However, when listing a hadith narration, KH. Misbah Musthofa did not include a sanad from the hadith.Kajian ini membincangkan tentang tafsir karya KH. Misbah Musthofa yang berjudul al-Iklil fi Ma’ani al-Tanzil. Dalam tafsir ini menggunakan metode tahlili dan corak dari tafsir ini jika dilihat dari beberapa pendapat mempunyai beberapa corak, tetapi dalam penulisan ini penulis mencantumkan corak sufistik dan adab al-Ijtima’i. Dalam menafsirkan sebuah ayat KH. Misbah Musthofa banyak melalui rasio (bi al-Ray’i). Tujuan kajian ini supaya masyarakat sentiasa berpedoman kepada al-Qur’an dalam kehidupan di dunia. Selain itu tafsir ini juga banyak mengkritik tentang masalah atau peristiwa yang terjadi dalam kalangan masyarakat.. Seperti yang penulis contohkan tentang larangan Keluarga Berencana atau perancangan keluarga. Menurut KH. Misbah Musthofa dengan mengaitkan peristiwa tersebut terhadap kisah Fir’aun. Kajian ini berbentuk kualitatif dengan analisis kepustakaan daripada al-Quran. Hasil kajian menunjukkan bahawa tafsir al-Iklil fi Ma’ani al-Tanzil merupakan salah satu dari penafsiran yang bercorak Nusantara dengan tafsirannya menggunakan aksara jawa pegon. Dalam penafsirannya, KH. Misbah Musthofa selalu menjelaskan makna ayat secara jelas dan terperinci, misalnya hubungan suatu ayat dengan ayat dan hadis-hadis. Namun, ketika mencantumkan sebuah riwayat hadis, KH. Misbah Musthofa tidak mencantum sanad dari hadis tersebut.